Green's functions with applications - Duffy, Dean G. (Studies in advanced mathematics, 2015)
This second edition systematically leads readers through the process of developing Green's functions for ordinary and partial differential equations. In addition to exploring the classical problems involving the wave, heat, and Helmholtz equations, the book includes special sections on leaky modes, water waves, and absolute/convective instability. The book helps readers develop an intuition about the behavior of Green's functions, and considers the questions of the computational efficiency and possible methods for accelerating the process.